Stratification and monitoring of natalizumab-associated progressive multifocal leukoencephalopathy risk: recommendations from an expert group. Issue 2 (22nd October 2015) - McGuigan, C; Craner, M; Guadagno, J; Kapoor, R; Mazibrada, G; Molyneux, P; Nicholas, R; Palace, J; Pearson, O R; Rog, D; Young, C A
Abstract : The use of natalizumab for highly active relapsing-remitting multiple sclerosis (MS) is influenced by the occurrence of progressive multifocal leukoencephalopathy (PML). Through measurement of the anti-JCV antibody index, and in combination with the presence or absence of other known risk factors, it may be possible to stratify patients with MS according to their risk of developing PML during treatment with natalizumab and detect early suspected PML using MRI including a diffusion-weighted imaging sequence. This paper describes a practical consensus guideline for treating neurologists, based on current evidence, for the introduction into routine clinical practice of anti-JCV antibody index testing of immunosuppressant-naïve patients with MS, either currently being treated with, or initiating, natalizumab, based on their anti-JCV antibody status. Recommendations for the frequency and type of MRI screening in patients with varying index-associated PML risks are also discussed. This consensus paper presents a simple and pragmatic algorithm to support the introduction of anti-JCV antibody index testing and MRI monitoring into standard PML safety protocols, in order to allow some JCV positive patients who wish to begin or continue natalizumab treatment to be managed with a more individualised analysis of their PML risk.